A foucauldian study of space and power in two novels by Nadine Gordimer - Shabanirad, Ensieh; Dadkhah, Mahtab (Penerbit Universiti Kebangsaan Malaysia, 2017)
This paper aims to study the relation between space and power in Nadine Gordimer’s first novel of the apartheid regime, The Lying Days (1953) and her first novel of the postapartheid era, None to Accompany Me (1994) in the light of Michel Foucault’s theory of space and power. The paper first introduces Gordimer and the concept of apartheid. Then, it states the common engagement of Foucault and Gordimer with the concepts of space and power in their work, the significance of the study and the limitations of the research. After offering the literature review, the researchers discuss Foucault’s theories and his key concept of heterotopias (other spaces) and the relation between his ideas and apartheid. After that, drawing on the theoretical insights of Foucault, the researchers explore how Gordimer’s selected novels display an ongoing and developing understanding of the importance of space as a way of explaining key questions of power, resistance and social organization and reflect on the geopolitics of apartheid and its policies of spatial control in South Africa. The researchers also explore how heterotopias as sites of social struggle and resistance challenge apartheid. The researchers examine space as a technique of control and domination, as well as a means of resistance.